1990
DOI: 10.1136/ard.49.5.323
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant systemic lupus erythematosus and ankylosing spondylitis.

Abstract: The case is reported of a 42 year old white woman meeting currently used diagnostic criteria for both ankylosing spondylitis and systemic lupus erythematosus (SLE). As found in a previously described similar case of a black man, HLA typing showed antigens associated with both SLE and seronegative spondyloarthropathy. This case thus supports the hypothesis that the two diseases occur together only when this rare combination of HLA antigens is present.The coexistence ofsystemic lupus erythematosus (SLE) and sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…Interestingly, most of the reported patients with the coexistence of SLE and AS, including the present case, are female (F/M: 6/3). In most cases, including the present case, SLE symptoms preceded those of AS (F/M: 5/4) (4,5,6,9). On the other hand, the association between HLA-B27 and AS is well known, and the HLA-B27 molecule plays a role in the pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, most of the reported patients with the coexistence of SLE and AS, including the present case, are female (F/M: 6/3). In most cases, including the present case, SLE symptoms preceded those of AS (F/M: 5/4) (4,5,6,9). On the other hand, the association between HLA-B27 and AS is well known, and the HLA-B27 molecule plays a role in the pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 88%
“…These two autoimmune rheumatologic diseases, which have a different aetiopathogenesis as well as diverse clinical and genetic characteristics, are rarely seen together. To the best of our knowledge, there are only 8 reported cases of the coexistence of SLE and AS in the English literature (3)(4)(5)(6)(7)(8)(9)(10). Here, we report another case with the coexistence of these two diseases.…”
Section: Introductionmentioning
confidence: 79%
“…Studies of haplotype frequency in white subjects have shown that the combination of the B27 antigen with the DR2 and/or DR3 antigens is quite rare [12]. Nashel et al [3] and Olivieri et al [5] each described the coexistence in a single patient of ankylosing spondylitis and SLE. In both cases, HLA typing showed the B27 antigen in combination with the DR2 and/or DR3 antigens [3,5].…”
Section: Discussionmentioning
confidence: 98%
“…Nashel et al [3] and Olivieri et al [5] each described the coexistence in a single patient of ankylosing spondylitis and SLE. In both cases, HLA typing showed the B27 antigen in combination with the DR2 and/or DR3 antigens [3,5]. The authors suggest that SLE and spondyloarthropathy may coexist only when this rare combination of genetically determined markers occurs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation